Case Report: Osteomyelitis of the Proximal Phalanx of the Finger in Patient With Ollier Disease - Lipatov, Konstantin; Melkonyan, George; Shekhter, Anatoly; Asatryan, Artur; Kholikov, Abduaziz; Fayzullin, Alexey (Frontiers in Surgery, 2021)
Ollier disease is a rare congenital pathology characterized by the growth of enchondromas in bones, accompanied with their deformities, fractures and the risk of malignancy. A 39-year-old patient with Ollier disease (acroform with lesions of hands and feet) suffered a rapid development of osteomyelitis of the proximal phalanx of the ring finger after a mosquito bite. The condition localized in the area of enchondroma. Surgical treatment included osteonecrectomy in the phalanx and enchondroma with excision of non-viable surrounding soft tissues, drainage of the surgical wound and the imposition of primary sutures. Morphological analysis confirmed the presence of ectopic embryonic cartilage specific for Ollier disease and the bone destruction. The excised tissues were infiltrated with immune cells and had signs of periosteal chronic inflammation including fibrosis and hyalinosis. These changes, which occurred long before the mosquito bite, became a favorable background for the development of a purulent infection.